Enhancing Critical Thinking and Learning Outcomes: The Impact of Differentiated Learning Strategies in Elementary School - Luluk Fidiasih; Eges Triwahyuni; Ahmad Zaki Emyus (Postgraduate, University of Mataram, 2025)
This study aims to create a simple Differentiated Learning Strategy (DSLS) to improve critical thinking skills and student learning achievement in elementary schools in Jombang Regency. This study aims to help teachers create an inclusive, interactive, and motivating environment for students by addressing the challenges of implementing DSLS and the Merdeka Curriculum policy. The method used is a quasi-experimental design with a non-equivalent approach. The assessment tools used consist of observation sheets based on Bloom's Taxonomy and learning outcome tests specifically designed to evaluate high-order thinking skills (HOTS) through C4 questions. Data analysis was carried out using repeated measure ANOVA to assess the effectiveness of the intervention. The results showed that the implementation of SDLS significantly improved critical thinking skills and student learning outcomes. This study significantly improves the quality of elementary education and serves as a guide for teachers to implement differentiated learning in other schools.